2004
DOI: 10.1556/avet.52.2004.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Soybean: feed quality and safety. Part 2: Pathology of soybean feeding in animals. A review

Abstract: Various animal models in farm and laboratory animals indicate the possible pathological effect of soybean feeding. Immunity and tolerance to oral soybean intake and a generalised meta-model of effects are discussed. It seems that FAO/WHO recommendations will have to be considered in assessing the biological value of soybean feed sources. Determination of hull content, antigenic potential, conglycinin and trypsin inhibitor content is warranted in view of the future component pricing of soybean meals.Key words: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…This may be caused by the higher fiber content and the presence of the trypsin inhibitor in vegetable proteins, as previously reported by Csaky and Fekete (2004). Furthermore, the experimental diets did not cause any detrimental effect on visceral weight of the experimental animals, which is similar to findings in other studies (Csaky and Fekete, 2004;Reis de Souza et al, 2007;Opapeju et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This may be caused by the higher fiber content and the presence of the trypsin inhibitor in vegetable proteins, as previously reported by Csaky and Fekete (2004). Furthermore, the experimental diets did not cause any detrimental effect on visceral weight of the experimental animals, which is similar to findings in other studies (Csaky and Fekete, 2004;Reis de Souza et al, 2007;Opapeju et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…Li et al (1991) and Csaky and Fekete (2004) have observed similar effects in weaned piglets fed soybean meal diets. Zhan et al (2008) and Shan et al (2012) observed that dietary supplementation of arginine improved intestinal mucosa development in weaning piglets.…”
Section: Ajavsmentioning
confidence: 66%
See 1 more Smart Citation
“…However, the presence of antigenic proteins such as glycinin, β-conglycinin and anti-nutritional factors such as TI and lectins in soybean could cause hypersensitivity for newly weaned piglets which may decrease nutrient availability and therefore restrict its’ inclusion in diets fed to weaning pigs (Li et al, 1990; Csaky and Fekete, 2004; Hao et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Their therapeutic and/or preventive virtue, based partly on the ability to bond with estrogenic or androgenic receptors, is exerted especially in anticancer mechanisms (prevention and lower incidence in hormone‐related types of cancer), regulation of cardiovascular complaints and osteoporosis, antimicrobial protection and alleviation of postmenopausal disorders (with the possible use as an alternative to hormone replacement therapy) . Although isoflavonoids have a considerable number of positive health effects, they were first noticed in the first half of the last century, when reproduction problems had been noted in animals grazing on clover‐rich pastures …”
Section: Introductionmentioning
confidence: 99%